A fuzzy logic and optimisation based approach for shipyard facility layout problem with consideration of risk, activity, and flow factors - Mustafa Kafali (Brodogradnja)
One of the crucial factors of shipbuilding in terms of production efficiency is the arrangement of workstations. Since shipyard design involves the layout of many workstations, an initial setup is helpful for the shipyard designer. This paper proposes a new methodology for determining the relative locations of shipyard workstations. The novelties of this study are the use of the Simulated Annealing (SA) approach for determining shipyard workstation’s relative locations, the use of fuzzy logic and metaheuristic optimisation together in the shipyard facility layout planning (FLP) domain, and the incorporation of safety concept into the shipyard FLP. The procedure for determining proximity rating involves both qualitative (activity) and quantitative (flow and risk) factors and employs fuzzy logic. The problem of determining the relative locations of workstations is treated as an optimisation problem. The proposed methodology successfully generated three distinct shipyard layouts. These include U, L, and I-shaped arrangements for profiled panel production, as well as an almost star-shaped branched arrangement for sub-block production. Results show that this approach offers beneficial alternative starting layouts for a shipyard designer.